The patio-groups”: a type of spatial organization inside a settlement of the late Intermediate period (1100-1400 ad) in the Vilcas Huamán province - Martinez Sulca, Winnie Celeste (2022)
The architectural study carried out, through the planimetric and topographic survey, in the Llaqtaqasa archaeological site, specifically in Sector B, yielded new data where the "Patio Groups" in addition to being the registered archaeological construction unit corresponds to a new type of organization space within a settlement of the Late Intermediate Period in the province of Vilcas Huamán (Ayacucho). This organization presents a closed spatial configuration where the enclosures and patios are the main components. This article will present the data obtained around this type of spatial organization where the different construction phases and internal circulation in the referred sector are also being considered.